2005
DOI: 10.1089/ham.2005.6.256
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Exercise–Hypoxia Challenge on GLUT4 Protein Expression in Rat Cardiac Muscle

Abstract: Altitude training is a frequently used method for enhancing endurance performance in athletes. But its acute effect on carbohydrate metabolism in cardiac muscle is unknown. In this study, we determined the acute effect of an exercise-hypoxia challenge on glycogen storage and GLUT4 protein expression in heart muscle. Sixteen male Sprague-Dawley rats were assigned to one of two groups: control (CTRL) and exercise-hypoxia (EX+HY). The exercise protocol consisted of swimming for 180 min twice, with a 45-min rest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…It was proposed that intermittent exercise in hypoxia, separated with passive (hypoxic) recovery, would stimulate glucose transport to a greater degree than the same exercise in normoxia. A mechanistic standpoint would support such a proposal in that as the exerciseinduced stimulus for glucose transporter (GLUT)-4 activation/translocation (37) wears off; it would be replaced by a hypoxic-induced stimulus known to cause the same glucose transport effect (22,24,44). Because glucose R a , R d , and arterialized blood glucose concentrations changed to a similar extent for both Nor5:5 and Hy5:5, it was concluded that intermittent exercise in hypoxia had no additive effect on short-term glucose metabolism in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that intermittent exercise in hypoxia, separated with passive (hypoxic) recovery, would stimulate glucose transport to a greater degree than the same exercise in normoxia. A mechanistic standpoint would support such a proposal in that as the exerciseinduced stimulus for glucose transporter (GLUT)-4 activation/translocation (37) wears off; it would be replaced by a hypoxic-induced stimulus known to cause the same glucose transport effect (22,24,44). Because glucose R a , R d , and arterialized blood glucose concentrations changed to a similar extent for both Nor5:5 and Hy5:5, it was concluded that intermittent exercise in hypoxia had no additive effect on short-term glucose metabolism in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal promoter plays a role in gluconeogenesis and lipogenesis while the distal promoter is important for anaplerosis in pancreatic β-cells and other tissues (18). Distinct translation regulation by alternative 5’ UTRs has been reported for a stress-responsive protein –dPrxI (28), for human neuronal nitric-oxide synthase (29), and for human proinsulin gene (30). The three promoters in the human PC gene giving rise to three different PC isoforms may allow for tissue specificity, for differential functional capacity, or for developmental stage-specificity as is the rule with other human and mammalian genes (18, 26, 31).…”
Section: Discussionmentioning
confidence: 99%
“…According to scientific reports, the primary aim of diabetes treatment is to achieve as stable glycaemic control as possible to prevent the long-term complications [30][31][32]. The ability of Hx to stimulate glucose uptake independently of muscle contraction has been presented in studies of animals [39], obese humans [40], and individuals with T2D [20,41]. However, combining Hx with muscle contractions seem to improve glycaemic control to a greater extent than the stimuli alone [20,39,42].…”
Section: Glycaemic Control In Response To Different Exercise Protocolsmentioning
confidence: 99%
“…The ability of Hx to stimulate glucose uptake independently of muscle contraction has been presented in studies of animals [39], obese humans [40], and individuals with T2D [20,41]. However, combining Hx with muscle contractions seem to improve glycaemic control to a greater extent than the stimuli alone [20,39,42]. In the study by Mackenzie et al [20,42] both continuous and intermittent exercise combined with Hx significantly reduced T2D patients' glycaemia and enhanced insulin sensitivity.…”
Section: Glycaemic Control In Response To Different Exercise Protocolsmentioning
confidence: 99%